English Language Teaching in Indonesia: A Continuous Challenge in Education and Cultural Diversity - M. Marcellino (TEFLIN, 2006)
The linguistic situations and conditions in Indonesia are quite complex by their own natures as more than seven hundred vernaculars with their various dialects from a great number of ethnic groups have been used as media of communication in the country. Accordingly, the success of English teaching in Indonesia cannot be freed from the studentsÃ¢â¬â¢ cultural backgrounds, values, customs, and beliefs as well as the political standpoint of the government regarding this foreign language. English language teaching has then undergone more than four changes in its curriculum since the countryÃ¢â¬â¢s independence and brought no significant impact upon the learning outcomes. This study reveals the substantial unconstructive influence of the studentsÃ¢â¬â¢ cultures and the non-conducive language environment affecting their language acquisition. Other aspects related to the teachersÃ¢â¬â¢ performance and class preparations equally contribute to the ineffective classroom interactions. This study offers some practical suggestions to cope with those problems.